CREATIVITY DOMINATION AS A KEY CHARACTERISTIC OF THE ANTI-CRISIS ACTIVITY - Aleksey M. Erokhin; Olga V. Kashirina (Вестник Северо-Кавказского федерального университета, 2022)
Anti-crisis practices, as well as student cognitive activity and teacher everyday creation, are full of creativity (со-creation), and are non-aloof forms of social being, that’s why they always are self-motivated and free.